KELAYAKAN PEMBANGUNAN PERKEBUNAN KELAPA SAWIT KOPERASI PERKEBUNAN TEMIGA SELUAS 5.200 HA DI KABUPATEN ACEH BARAT - Rusdi Faizin (Universitas Teuku Umar, 2017)
Oil palm with main product CPO and KPO be commodity that has good opportunity in domestic and national market. Oil palm plantation project Temiga co-operation of Plantation planned built at West Aceh as efforts revitalisasi economics pasca conflict, earthquakes and tsunami oil palm plantation commodities broadly 5,200 hectare at five districts are Sungai Mas, Main Woyla, Eart Woyla, West Woyla and Arongan Lambalek West Aceh Sub-province. The lands planned are cooperation members of Temiga Co-operation with land suitability S-1, S-2 and S3 clases, so that production that planned are average production from three levels suitability. With totalize investment Rp. 208,000.000,000.- for 5,200 hectare or Rp. 40,000,000,- per hectare, feasibility analysis shows that project suitable to executed because in level DF 12 % is got NPV Rp.225,114,199,000, -, B/C Ratio 2.18 and IRR 15.00 % with Pay Back of Period 8 years and 9 months project age-. Furthermore project will can to close totalize investmen in the year-15 project with instalment 25 % from net benefit project. With profit sharing scheme up year-15 net benefit of project 50 % investor and 50 % for co-operation. Totalize earnings from benefit sharing for investor are Rp. 465,842,368,000,- during project period. Oil palm plantation development Temiga Co-operation of Plantation has big opportunity to increase society economics at five project location districts because co-operation member society as garden owner later, also projectwill increase West Aceh subprovince region economics.